Mass-media y mensajes en la aldea global. Los géneros del ciberperiodismo - Moreno Espinosa, Pastora (Estudios sobre el Mensaje Periodístico, 2006)
The information, the interpretation and the opinion resurge as exclusive arms of the press printed, from the point of view of the content, as opposed to the speed and update of the audio-visual and electronic informative message. From the formal point of view, the image is the great protagonist of the newspaper. The argumentative predominance of visual resources on textual language, sorts, the media of services, etc., define the printed press of the last years. The information in written press has been in the last decades overflowed by the instantaneity that offer the means that contribute rapidity of transmission. The written press must adopt new formulas to catch and to maintain the interest of its readers, formulas that are also translated in changes not only in the journalistic language but in the style and informative content of present newspapers. We are before the crossroads of the “digital revolution of the media”. For that reason, one requires a new tone and direction of language in the press able to respond to a new and complex way to conceive the life. For the renovation of the language in the media it would be necessary to solicit to mobilize his rigidity, to give him to flexibility and wealth adapting to the new times of the digital press. In our days it is necessary to redefine the paper of opinion and mass media and its complementariness in informative tasks, objective of this article that occupies to us.